2019
DOI: 10.1002/cssc.201901566
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Thermoelectric Conversion with Polysulfide as Redox Species

Abstract: Thermocells convert waste heat to electricity without any pollution; however, the high cost and corrosivity of redox species hinder their commercialization. In this work, a thermocell that utilizes abundant polysulfide as redox species was demonstrated for the first time. 1‐Butyl‐1‐methylpyrrolidinium polysulfide [(P14)2S3] was synthesized, and the redox species were prepared by the addition of sulfur to the (P14)2S3 solution in DMSO. In thermoelectric measurements, the Seebeck coefficient changed from −0.68 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…For example, Jia et al observed different ratios of water to ionic liquid in binary systems could yield either positive or negative S e(tg) values; 18 Liang et al observed different ratios of [S 3 ] 2− to S 8 in DMSO could also result in different S e(tg) signs. 19 Aldous et al demonstrated how the ferrocene/ferrocenium redox couple could be made to have a positive or negative S e(tg) in ionic liquids by covalently tethering on appropriately charged groups. 20 For actual devices (or thermocells) with multiple thermogalvanic cells in-series to boost the voltage output, one device was recently reported where the S e(tg) of the aqueous I − /[I 3 ] − redox couple (+0.71 mV K −1 ) was inverted into the p-type direction upon introduction of poly-N-isopropylacrylamide, to −1.91 mV K −1 .…”
Section: δV δT ¼ àS Eðteþ ð1þmentioning
confidence: 99%
“…For example, Jia et al observed different ratios of water to ionic liquid in binary systems could yield either positive or negative S e(tg) values; 18 Liang et al observed different ratios of [S 3 ] 2− to S 8 in DMSO could also result in different S e(tg) signs. 19 Aldous et al demonstrated how the ferrocene/ferrocenium redox couple could be made to have a positive or negative S e(tg) in ionic liquids by covalently tethering on appropriately charged groups. 20 For actual devices (or thermocells) with multiple thermogalvanic cells in-series to boost the voltage output, one device was recently reported where the S e(tg) of the aqueous I − /[I 3 ] − redox couple (+0.71 mV K −1 ) was inverted into the p-type direction upon introduction of poly-N-isopropylacrylamide, to −1.91 mV K −1 .…”
Section: δV δT ¼ àS Eðteþ ð1þmentioning
confidence: 99%
“…UV–vis spectra of Li 2 S 6 solution before and after soaking with MOF-808-AQ are shown in Figure S7. The disappearance of S 6 2– peak (around 350 nm) , in the supernatant demonstrates that MOFs possess the ability to uptake lithium polysulfides from solution.…”
Section: Resultsmentioning
confidence: 93%
“…43,44 To confirm, MOF-808-AQ powder is soaked in a polysulfide solution (10 mM Li 2 S 6 in 1:1 DOL/DME) for 24 h. The color of the solution turned from orange to transparent (Figure S6), indicating the polysulfides have diffused into the MOF pores. UV−vis spectra of 45,46 in the supernatant demonstrates that MOFs possess the ability to uptake lithium polysulfides from solution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In this Minireview, we divided the molecular technologies used in thermocells into four categories: redox entropy, molecular recognition, phase separation, and phase transition. The absolute voltages obtained at the maximum Δ T in each study are summarized in Figure 17 [11, 12, 14–21, 33, 40, 42, 43, 68, 69, 71, 72, 76–91] . As a guideline, we added a line representing | S e |=2 mV K −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The S e value of the thermocell is proportional to its ΔS value before and after the redox reaction (ΔS rc ). ΔS rc can be induced by various factors, such as spin transitions, [11] change of the solvation structure, [40] formation or breakage of polyanionic chains (such as polyiodide and polysulfide), [41,42] and protonation or deprotonation of the redox species. [43] Weaver and co-workers carried out the first systematic studies on the ligand and solvent effects on the ΔS rc of transition-metal complexes.…”
Section: Ligand and Solvent Effects On The Entropy Change Of A Transi...mentioning
confidence: 99%